2008
DOI: 10.14238/pi48.1.2008.33-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between age and serum ferritin level with bone age deficit in children with thalassemia major

Abstract: Background Multiple blood transfusions in thalassemia patientslead to iron overload in bone tissue. Iron overload can bedetermined by serum ferritin measurement. Several studies haveevaluated association between serum ferritin level and growth,but without bone age examination.Objective To determine the association between age and serumferritin level with bone age in children with thalassemia major.Methods This study was conducted at Hasan Sadikin HospitalBandung during March-May 2007. We performed physicalexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…High serum ferritin levels and iron overload in puberty were reported to cause short stature and delayed body growths in thalassemia major patients [22]. Iron overload can prohibit bone metabolisms leading to growth disorders [23], [24]. In our present study, as thalassemia is a chronic form of anaemia, the weight difference is expected compared to control.…”
Section: Discussionmentioning
confidence: 58%
“…High serum ferritin levels and iron overload in puberty were reported to cause short stature and delayed body growths in thalassemia major patients [22]. Iron overload can prohibit bone metabolisms leading to growth disorders [23], [24]. In our present study, as thalassemia is a chronic form of anaemia, the weight difference is expected compared to control.…”
Section: Discussionmentioning
confidence: 58%
“…[8] Other studies showed Subjects with bone age difference <36 months mostly had serum ferritin level <5,000 ng/dL, while most subjects with bone age difference >36 months had serum ferritin level =5,000 ng/dL. [9] CONCLUSION:…”
Section: Resultsmentioning
confidence: 96%
“…These results were similar with a study that showed no associations between serum ferritin and bone age. 29 Most subjects with impaired glucose tolerance had ferritin levels between 1,001 and 5,000 ng/ dL. Subjects with DM were distributed among the 1,001 -10,000 ng/dL ferritin groups.…”
Section: Discussionmentioning
confidence: 95%